1992
DOI: 10.1136/bmj.304.6826.541
|View full text |Cite
|
Sign up to set email alerts
|

Relation of bronchioloalveolar carcinoma to tobacco.

Abstract: groups of men non-employed through illness are likely to be heterogeneous with regard to type and severity of illness. Thus for some men, but not all, illness will be directly responsible for their weight loss and reduction in smoking and drinking.This study indicates the need to take account of the long term effects of higher levels of smoking and alcohol consumption and less exercise before unemployment when comparing mortality and morbidity among groups of unemployed and employed people, such as in the Offi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
27
1

Year Published

1995
1995
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 16 publications
2
27
1
Order By: Relevance
“…Bronchioalveolar carcinoma (BAC) has been a rare tumor suspected to be unrelated to cigarette smoking. However, a recent study documented a clear dose-response relationship between BAC and years of cigarette smoking (34).…”
Section: Introductionmentioning
confidence: 98%
“…Bronchioalveolar carcinoma (BAC) has been a rare tumor suspected to be unrelated to cigarette smoking. However, a recent study documented a clear dose-response relationship between BAC and years of cigarette smoking (34).…”
Section: Introductionmentioning
confidence: 98%
“…The incidence of BAC has risen steadily over the last decades along with the general increase in frequency of adenocarcinomas, reaching up to 24% of lung cancer cases in some clinical series [2]. BAC tends to occur more frequently in younger patients, women and non-smokers [3]. A variety of environmental factors have been linked to the etiology of BAC [4].…”
Section: Introductionmentioning
confidence: 99%
“…They also suggested that three clinical subtypes of bronchioloalveolar carcinoma can be identified: mucinous, nonmucinous, and sclerotic. Bronchioloalveolar carcinoma is likely to be less related to cigarette smoking than many other cell types of lung cancer (29)(30)(31).…”
Section: Histologic Patternsmentioning
confidence: 99%